Assessing the potentials of bacterial antagonists for plant growth promotion, nutrient acquisition, and biological control of Southern blight disease in tomato. - Farjana Sultana; M Motaher Hossain (PLoS ONE)
Southern blight of tomato caused by Sclerotium rolfsii can cause severe plant mortality and yield losses. The use of rhizobacteria for the biological control of Southern blight disease is a potent alternative to chemical fungicides. Although rhizobacteria are prolific candidates, comprehensive reports regarding their use in tomato disease management are limited. The present study screened six rhizobacterial strains for antagonism against S. rolfsii in dual culture and culture filtrate assays. The selected promising strains were tested further for plant-growth-promoting and biocontrol potentials under in vitro, greenhouse, and field conditions. Of the six strains screened, Stenotrophomonas maltophilia PPB3 and Bacillus subtilis PPB9 showed the superior performance displaying the highest antagonism against S. rolfsii in dual culture (PPB3 88% and PPB9 71% inhibition), and culture filtrate assays (PPB3 53-100% and PPB9 54-100% inhibition at various concentrations). Oxalic acid produced by S. rolfsii was significantly inhibited by both rhizobacteria and supported their growth as a carbon source. The strains produced hydrogen cyanide, chitinases, siderophores, biofilm, and indole acetic acid. They showed the potential to solubilize phosphate and fix nitrogen. Seed treatment with S. maltophilia PPB3 and B. subtilis PPB9 improved seed germination and tomato seedling vigour. Significant increases in plant growth, chlorophyll contents, and N, P, and K concentrations were attained in bacterized plants compared to non-treated controls. The application of antagonists on container-grown seedlings in a greenhouse environment and field-grown tomato plants reduced symptoms of damping-off and Southern blight. The sclerotial counts decreased significantly in these soils. Bacteria-inoculated plants had a higher yield than those in the non-treated control. Bacteria colonized the entire roots, and their populations increased significantly in the protected plants. The results show the potential capabilities of S. maltophilia PPB3 and B. subtilis PPB9 for growth promotion, nutrient acquisition, and biocontrol of southern blight disease in tomatoes.